Design, Kinematic Optimization, and Evaluation of a Teleoperated System for Middle Ear Microsurgery - Mathieu Miroir; Yann Nguyen; Jérôme Szewczyk; Olivier Sterkers; Alexis Bozorg Grayeli (The Scientific World Journal)
Middle ear surgery involves the smallest and the most fragile bones of the human body. Since microsurgical gestures and a submillimetric precision are required in these procedures, the outcome can be potentially improved by robotic assistance. Today, there is no commercially available device in this field. Here, we describe a method to design a teleoperated assistance robotic system dedicated to the middle ear surgery. Determination of design specifications, the kinematic structure, and its optimization are detailed. The robot-surgeon interface and the command modes are provided. Finally, the system is evaluated by realistic tasks in experimental dedicated settings and in human temporal bone specimens.